Vessel In-Water Cleaning or Treatment: Identification of Environmental Risks and Science Needs for Evidence-Based Decision Making - Scianni, Chris; Georgiades, Eugene (Frontiers in Marine Science, 2019)
The accumulation of aquatic organisms on the wetted surfaces of vessels (i.e., vessel biofouling) negatively impacts world-wide shipping through reductions in vessel performance and fuel efficiency, and increases in emissions. Vessel biofouling is also a potent mechanism for the introduction and spread of marine non-indigenous species. Guidance and regulations from the International Maritime Organization, New Zealand, and California have recently been adopted to address biosecurity risks, primarily through preventive management. However, appropriate reactive management measures may be necessary for some vessels. Vessel in-water cleaning or treatment (VICT) has been identified as an important tool to improve operating efficiency and to reduce biosecurity risks. VICT can be applied proactively (i.e., to prevent the occurrence of, or to remove, microfouling (i.e., slime) or prevent the occurrence of macrofouling organisms - large, distinct multicellular organisms visible to the human eye), or reactively (i.e., to remove macrofouling organisms). However, unmanaged VICT includes its own set of biosecurity and water quality risks. Regulatory policies and technical advice from California and New Zealand have been developed to manage these risks, but there are still knowledge gaps related to the efficacy of available technologies. Research efforts are underway to address these gaps in order to inform the regulatory and non-regulatory application of VICT.